2021
DOI: 10.3390/ma14195616
|View full text |Cite
|
Sign up to set email alerts
|

Rigid Polyurethane Foams Modified with Biochar

Abstract: This paper presents results of research on the preparation of biochar-modified rigid polyurethane foams that could be successfully used as thermal insulation materials. The biochar was introduced into polyurethane systems in an amount of up to 20 wt.%. As a result, foam cells became elongated in the direction of foam growth and their cross-sectional areas decreased. The filler-containing systems exhibited a reduction in their apparent densities of up to 20% compared to the unfilled system while maintaining a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…The foaming process is an important step that affects the performance of rigid PUR foams [ 42 ]. Table 1 presents the results of the processing times of the tested foams and the maximum temperature that was obtained during foaming.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The foaming process is an important step that affects the performance of rigid PUR foams [ 42 ]. Table 1 presents the results of the processing times of the tested foams and the maximum temperature that was obtained during foaming.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in viscosity of PUR systems under the influence of the filler is also considered to be the main reason for the increase in these times, which consequently limits proper cell expansion. On the basis of studies conducted so far, it can be concluded that with the increase in the number of various types of fillers introduced into the microstructure of foams, higher viscosity of PUR systems and an increase in their processing times are observed [ 12 , 15 , 31 , 42 , 44 , 45 , 46 , 47 , 48 , 49 ]. Furthermore, the functional groups of fillers can react with isocyanate groups, which can affect the proper stoichiometry of the reaction and limit the release of blowing agents (CO 2 ) [ 15 , 44 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Modified PU resins are widely used in various applications, such as coatings, foams, medicinal products, thermal insulation, and adhesives [2][3][4][5]. Due to its superior properties compared to other polymers, such as high mechanical strength, flexibility at low temperatures, and the ability to be formed as a rigid, semi-rigid, or flexible foam with various densities, PU has become one of the most important type of resins used in various value-added applications, with an estimated global market volume of approximately 24 million tons in 2020 [6,7]. The synthesis of PU is carried out through a condensation reaction between isocyanates and polyols, where the main ingredients of the polymer to produce polyurethane are derived from refining crude oil and coal [8].…”
Section: Introductionmentioning
confidence: 99%
“…The anisotropy coefficient values for PP40-PP44 foams indicated differences in the shape of the cells analysed in the cross-section parallel and perpendicular to the foam growth direction. Cells in the cross-section parallel to the foam growth direction reach an anisotropy coefficient above 1 and are characterised by an elongated shape [36]. In contrast, cells in the perpendicular section have a factor of less than 1.…”
Section: Cell Structure and Physical Properties Of Developed Rigid Pur Foamsmentioning
confidence: 99%